An exploratory study on the effects of rearing system and plumage colour on performance, carcass characteristics and meat quality of local turkeys (International Journal of Health, Animal Science and Food Safety, 2019)
In a bid to improve the productive potentials of local turkeys in developing countries, a total of 240 unsexed day-old poults arranged in a 2 × 2 factorial layout into 4 treatments with two rearing systems (indoor and outdoor) and two plumage colours (white and black) were used for this study. Poults were brooded for 4 weeks followed by an acclimatization period of 2 weeks in the two different rearing systems before the commencement of the study which lasted 10 weeks. Each treatment consisting of 60 birds was further sub-divided into six replicates of 10 birds per replicate. Data obtained were subjected to Analysis of Variance in a Completely Randomized Design. Results on performance in the grower phase showed turkeys reared in indoor system recorded significantly (p
Keywords: Local turkey; Plumage; Indoor; Outdoor